Bis(2-nitrophenyl)methane - Janzen, Daron E. (International Union of Crystallography, 2014)
In the title compound, C(13)H(10)N(2)O(4), the nitro groups are twisted significantly relative to the benzene rings [dihedral angles = 16.64 (18) and 28.02 (11)°]. The benzene groups are nearly perpendicular to each other [dihedral angle = 87.72 (6)°]. Short intermolecular N⋯O and C⋯O [2.981 (2) and 3.060 (2) Å, respectively] contacts suggest possible weak π-interactions between nitro groups and between benzene and nitro groups. In addition, there are π–π interactions between one benzene group and an inversion-related equivalent [interplanar separation = 3.494 (2) Å].